Gayutan Rondo Alla Turca Karya WA. Mozart sebagai Iringan dalam Film Amadeus - Panggabean, Ance Juliet; Simangunsong, Emmi; Batubara, Junita (Institut Seni Indonesia Yogyakarta, 2023)
ABSTRACTThe Use of WA Mozart's Gayutan Rondo Alla Turca in the Film Amadeus. This study describes the interconnection of Rondo music as an accompaniment in Amadeus film to the melodic structure of scene footage produced by HD Film Tributes and explains the form of Rondo which consists of six parts involving displayed scene expressions. The authors implemented qualitative approach with descriptive method in which the authors conducted literature review as well as observation through musical scores and YouTube channel to attain thorough results of field studies and documentation. Furthermore, the authors also conducted an analysis that began with the description of the film structure of the Rondo Alla Turca musical composition. The analysis was carried out by observing each scene footage of used melodic structure to form feelings and aesthetics in the film. The results of the study reveal that the melodic structure used in each scene creates feelings and aesthetics in Amadeus film since musical accompaniment plays an essential role in conveying the story of the film. In addition, the role of musical accompaniment is inherently employed to highlight the tones in Rondo Alla Turca music and visuals have the ability to provide a deeper and more complex interpretation of emotional content in every scene of Amadeus.ABSTRAKKajian ini mendiskripsikan gayutan atau hubungan musik Rondo sebagai iringan dalam film Amadeus terhadap struktur melodi dengan cuplikan adegan yang diproduksi oleh HD Film Tributes dan bentuk Rondo yang terdiri dari enam bagian dengan ekspresi adegan yang ditampilkan. Adapun metode yang digunakan dalam penelitian adalah deskriptif kualitatif dimana peneliti melakukan telaah pustaka, melakukan observasi melalui skor musik, channel youtube untuk mendapat hasil kajian lapangan yang optimal dan dokumentasi. Selain itu peneliti juga melakukan analisis yang dimulai dengan penjabaran struktur film terhadap komposisi musik Rondo Alla Turca. Analisis dilakukan dengan pengamatan antara setiap cuplikan adegan terhadap struktur melodi yang digunakan untuk membetuk perasaan dan estetika dalam film. Hasil penelitian menunjukkan bahwa struktur melodi yang digunakan dalam setiap cuplikan adegan membentuk perasaan dan estetika dalam film Amadeus, iringan musik memegang peranan penting dalam mengusung cerita film Amadeus, peran iringan musik secara inheren digunakan untuk menyoroti nada-nada dalam musik Rondo Alla Turca dan visual memiliki kemampuan untuk memberikan makna interpretasi konten emosional yang lebih dalam dan kompleks dalam setiap adegan fim Amadeus.